Ligand Synthesis Catalyst and Complex Metal Ion: Multicomponent Synthesis of 1,3-Bis(4-phenyl-[1,2,3]triazol-1-yl)-propan-2-ol Copper(I) Complex and Application in Copper-Catalyzed Alkyne-Azide Cycloaddition - María Teresa Ramírez-Palma; Jesús Segura-Arzate; Gustavo López-Téllez; Erick Cuevas-Yañez (Journal of Chemistry)
A new bistriazole copper complex was synthesized by direct treatment of an alkyne, an azide, and CuI as copper salt through in situ ligand formation under a multicomponent reaction process. This complex was analyzed by XPS, TGA, DSC, and SEM techniques and revealed a triangular-shaped morphology, high thermal stability, and catalytic power in CuAAC reactions, requiring only 2.5% mol catalyst to afford 1,2,3-triazoles in good yields which can be reused at least for 4 cycles.